Abelhas visitantes florais de Richardia grandiflora (Rubiaceae) ao longo de um gradiente urbano-rural - Cruz, Renata Marinho (2013)
Increasing urbanization is among the main drivers of the loss and fragmentation of habitats, that affect pollinator communities and change the plant-pollinator interactions. Although studies focusing on the influence of landscape on pollinators have increased , in Brazil this knowledge is incipient. Here, we analysed the bee visitors and reproductive success of Richardia grandiflora (Cham. & Schltdl.) Steud along an urban-rural gradient, relating to possible changes in the plant-pollinator interactions. This study was carried out in six areas located in the state of Paraíba, belonging to three different categories: urban, peri-urban and rural areas. We estimated the percentage of vegetation cover (woody and herbaceous-shrub), impervious surfaces, bare soil and water, in two spatial scales. Moreover, bee visitors of the flowers of R. grandiflora were observed monthly since February 2012 until January 2013, and the species composition, richness, frequency of occurrence and number of visits was recorded. Finally, we estimated the reproductive success from pollination treatments (open-pollination and supplementary cross-pollination) to obtain the Reproductive Efficacy of R. grandiflora in each area. In the clusters from the landscape characterization and species composition the urban areas were differentiated from the remaining, but peri-urban and country areas were not differentiated from each other. The little change in the richness of eusocial bees and the number of visits by stingless bees along the urban-rural gradient indicated good tolerance to urbanization. Non-eusocial bees had higher richness and frequency in rural and peri-urban areas. Moreover, the positive correlation between the number of non-eusocial bee visits and herbaceous-shrub vegetation, in the smallest spatial scale, suggests a greater influence of the local landscape on these species. The introduced species Apis mellifera had a higher frequency in urban areas, which may be related to lower availability of resources, as well as its ecological flexibility and competitive power. Finally, rural areas had the highest rates of Reproductive Efficacy while urban areas showed lower values. Possibly, A. mellifera was not as efficient as a native pollinator species, which may be a consequence of the fragmentation of the populations of Richardia grandiflora in the most urbanized areas.